ANALISIS DESAIN KEMASAN PEWANGI PAKAIAN MOLTO ANTI KUSUT PURPLE - Elida Christine (JURNAL Dasarrupa: Desain dan Seni Rupa, 2022)
Molto Anti-Tangled Purple clothing fragrance products are interesting to discuss because they have advantages in terms of packaging design that are visually related to elements of lines, shapes, colors, typography, and materials compared to other competitors. Molto is the first anti-wrinkle product in Indonesia that is easy to use. This Molto product continues to innovate in packaging design. Among them in this Molto product is a new logo that is simple and modern, the shape of the triple care serum icon and the existence of a QR Code for information on the use of this clothing softener to make it easier for consumers. The dimensions of Molto's product packaging design shape, namely spray bottles and refill pouches can provide practicality to its users. The color of Molto's product packaging design and its luxurious and elegant fragrance is the attractions of Molto Anti-Tangled Purple products.